Resilient teachers, resilient schools : building and sustaining quality in testing times - Day, Christopher, 1943-; Gu, Qing. (New York : Routledge, 2013)
'This book unpicks the complex, dynamic blend of individuals' psychological and professional assets, workplace conditions and leadership support which enable teachers who stay in teaching to continue to make a difference in their careers, regardless of shifts in policy, workplace, professional and personal circumstances. Whilst much has been written over the years about teacher stress and burnout, there is very little research which reports on the conditions which are essential for teachers to sustain their commitment and effectiveness over their professional lives, in contexts of challenge and change. Drawing upon a range of educational, psychological, socio-cultural and neuro-scientific research, together with vivid accounts from teachers in a variety of primary and secondary schools internationally, and from their own research on teachers' work and identities, the authors discuss the dynamic nature, forms and practices of teacher resilience. They argue that resilience in teachers is not only their ability to bounce back in extremely adverse circumstances but that it is the capacity of teachers for everyday resilience which enables them to sustain their commitment and effectiveness in responding positively to the unavoidable uncertainties inherent of their professional lives. The authors conclude that resilience in teachers can be nurtured by the intellectual, social and organisational environments in which teachers work and live, rather than being simply a personal attribute or trait, determined by nature. Resilient Teachers, Resilient Schools will be of key interest to policy makers, head teachers, teachers and training and development organisations who wish to improve quality and standards in schools'--
'This book unpicks the complex, dynamic blend of individuals' psychological and professional assets, workplace conditions and leadership support which enable teachers who stay in teaching to continue to make a difference in their careers, regardless of shifts in policy, workplace, professional and personal circumstances. Whilst much has been written over the years about teacher stress and burnout, there is very little research which reports on the conditions which are essential for teachers to sustain their commitment and effectiveness over their professional lives, in contexts of challenge and change. Drawing upon a range of educational, psychological, socio-cultural and neuro-scientific research, together with vivid accounts from teachers in a variety of primary and secondary schools internationally, and from their own research on teachers' work and identities, the authors discuss the dynamic nature, forms and practices of teacher resilience. They argue that resilience in teachers is not only their ability to bounce back in extremely adverse circumstances but that it is the capacity of teachers for everyday resilience which enables them to sustain their commitment and effectiveness in responding positively to the unavoidable uncertainties inherent of their professional lives. The authors conclude that resilience in teachers can be nurtured by the intellectual, social and organisational environments in which teachers work and live, rather than being simply a personal attribute or trait, determined by nature. Resilient Teachers, Resilient Schools will be of key interest to policy makers, head teachers, teachers and training and development organisations who wish to improve quality and standards in schools'--
Bookline/Prof Dr Nor Aishah Buang/Fakulti Pendidikan/e-mal: noraishah1962@gmail.com/Timbalan Dekan/(H/P): 019-3345709/Pameran Fakulti Pendidikan/Tarikh Pemilihan : 25-26-27/2/2014.
Keywords: Teachers -- Psychology; Resilience (Personality trait).